The Production of SCC with Low-Cost Using Minimum Amount Superplasticizer and Limestone Powder - Türk, Kazım; Turğut, Paki; Çelik, Bilal (Fırat University, 2015)
In this study, it was considered 3 different ready mix concrete companies producing conventional concrete (CC) in Sanliurfa, Turkey. Later, self-consolidating concrete (SCC) including same aggregates as those of conventional concrete was produced using minimum amount superplasticizer based on polycarboxylic acid and limestone powder (LSP) that exists in large quantities in Sanliurfa, Turkey. Slump-flow and T50 tests were performed for SCC mixtures containing 500 kg/m³ powder. After the specimens produced was demoulded, these was stored under water at 20±3 0C for 28 days and then tested for compressive strength. Finally, it was seen that it can be produced SCC at lower cost than CC when it was done cost-benefit analysis of CC produced by ready mix concrete companies and SCC having same strength (C25 ve C30) as those of CC.

Bu çalışmada, Şanlıurfa’daki 3 hazır beton firmasının ürettikleri farklı dayanımdaki geleneksel sıkıştırılan beton (GSB) karışımları dikkate alındı. Daha sonra, bu karışımlarda kullanılan benzer agregalar ile düşük miktarda polikarboksilat esaslı süper akışkanlaştırıcı ve Şanlıurfa’da oldukça yüksek rezerve sahip kireçtaşı tozu (KTT) kullanılarak kendiliğinden yerleşen beton (KYB) karışımları üretildi. 500 kg/m³ toz malzeme içeren karışımlar için EFNARC’ın belirlediği çökme-yayılma ve T50 deneyleri yapıldı. Numuneler 24 saat kalıpta bekletildikten sonra 28 gün 20±3 0C suda kür edildi ve basınç testine tabi tutuldu. Sonuç olarak, hazır beton firmalarının ürettikleri GSB ile benzer dayanımdaki (C25 ve C30) KYB karışımlarının fayda/maliyet analizleri yapıldığında GSB’den daha düşük maliyette KYB elde edildiği görüldü.
En az Miktarda Süper Akışkanlaştırıcı ve Kireçtaşı Tozu Kullanarak Düşük Maliyetli KYB Üretimi